PENGARUH INVESTASI DAN TENAGA KERJA SERTA INFLASI TERHADAP PERTUMBUHAN EKONOMI DI KALIMANTAN BARAT - B01108084, MAR SURIANI (Jurnal Pembangunan dan Pemerataan, 2013)
This study aimed to analyze the effect of Investment and Labor Against Inflation And Economic Growth In 1996 to 2010. With the goal is to determine how much influence the variable investment and employment and inflation, on economic growth. The analysis used is linear regression analysis with the aid of a computer program eviews 4.1. For the purpose of the study used secondary data in the form of time series from 1996 to 2010. Data obtained from the Central Statistics Agency (BPS), journals, books, and other research. Statistical tests include test coefficient of determination (R2) , F test and t-test, and test the assumptions of classical multicollinearity, autocorrelation and heterocedastisity. The results showed that the coefficient of determination (R2) between the variable investment and employment as well as inflation has a very strong connection to economic growth, and the F-test conducted between the variables have the effect of investment and employment and inflation on economic growth. In parsil t test investment variables (X1i) and labor (X2i) significant effect on economic growth, but inflation variable (X3i) were not significant to economic growth. Meanwhile, Based on testing known classical assumption that the test contained multicollinearity not multicollinearity and autocorrelation test contains elements of positive autocorrelation, as well as heterocedastisity not contain heterocedastisity. Keywords: Investment and Labor Against Inflation And Economic Growth In West Kalimantan